Black in-migration from the Eastern Cape into the Cape Metropolitan area : profile of the migrant and reasons for moving - Britz, Andre Alfrieda (Stellenbosch : Stellenbosch University, 2012)
Thesis (MA)--Stellenbosch University, 2002.